2018
DOI: 10.1302/2058-5241.3.170066
|View full text |Cite
|
Sign up to set email alerts
|

Weight-bearing cone beam CT scans in the foot and ankle

Abstract: The 3D anatomical complexity of the foot and ankle and the importance of weight-bearing in diagnosis have required the combination of conventional radiographs and medical CT.Conventional plain radiographs (XR) have demonstrated substantial limitations such as perspective, rotational and fan distortion, as well as poor reproducibility of radiographic installations. Conventional CT produces high levels of radiation exposure and does not offer weight-bearing capabilities.The literature investigating biometrics ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
64
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(70 citation statements)
references
References 46 publications
0
64
0
2
Order By: Relevance
“…Among the previously mentioned radiological methods, the measurement of the calcaneal moment arm for inframalleolar alignment The insole has a slightly elevated heel pad (asterisks), a medial wedge to correct the valgus angulation of the hindfoot (arrows) and a specific medial longitudinal support to sustain the plantar arch (arrow head) in a posterior radiographic view of the alignment of the hindfoot [16][17][18][19][20] and the medial distal tibial angle in an anterior view that uses the whole lower leg image are the most utilized. 21 In our sample of haemophilia patients, usually subjected to multiple radiographs during their life and without planned surgery, we considered that physical examination allowed us to determine adequately the indication of an orthotic treatment.…”
Section: Materials S and Me Thodsmentioning
confidence: 99%
“…Among the previously mentioned radiological methods, the measurement of the calcaneal moment arm for inframalleolar alignment The insole has a slightly elevated heel pad (asterisks), a medial wedge to correct the valgus angulation of the hindfoot (arrows) and a specific medial longitudinal support to sustain the plantar arch (arrow head) in a posterior radiographic view of the alignment of the hindfoot [16][17][18][19][20] and the medial distal tibial angle in an anterior view that uses the whole lower leg image are the most utilized. 21 In our sample of haemophilia patients, usually subjected to multiple radiographs during their life and without planned surgery, we considered that physical examination allowed us to determine adequately the indication of an orthotic treatment.…”
Section: Materials S and Me Thodsmentioning
confidence: 99%
“…In fact, bone orientation measurements in weight-bearing condition, both in absolute and relative terms, can now reveal the skeletal architecture in 3D, with the necessary accuracy and repeatability [ 16 ]. It has been also demonstrated that, with respect to standard computed tomography, radiation doses are smaller, device ergonomics and portability are better, and overall costs are smaller with the new technique [ 17 19 ] and these instruments are expected to be used extensively for clinical and biomechanical measurements of the foot in the next decades.…”
Section: Introductionmentioning
confidence: 99%
“…With the excellent depiction of the osseous tissue and the establishment of dedicated extremity scanners, CBCT provides several advantages over conventional multidetector CT (MDCT), particularly for trauma imaging [4]. Current literature on CBCT is mostly focused on lower extremity and spine imaging under weight-bearing conditions [5][6][7]; however, upper extremity imaging benefits from CBCT as well.…”
Section: Introductionmentioning
confidence: 99%